PENGARUH SUNGKUP DAN MULSA TERHADAP PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium. Ascalonicum.L) KULTIVAR NAPU - Regal, Moh; Fathurrahman, Fathurrahman; Basri, Zainuddin (AGROTEKBIS, 2017)
This research was conducted in Petimbe Village, Palolo District, Sigi Regency, Central Sulawesi Province. It held in July to September 2015. This research used Split Plot Design. The main plot was sheiter (N0) = Not in sheiter and (N1) = in sheiter and sub plots were various types of much (M0) = no mulch (M1) = rice straw mulch (M2) =black plastic mulch (M3) = silver plastic mulch. The observation variablewere height of plants (cm),at age of 30 and 40 DAP,number of leaves at age of 30 and 40 DAP, weight of fresh tubers per clump, and weight of fresh tuber per 5 clumps (g). The result of the research showed that the treatment of various types of mulch had no real effect on the growth of Napu cultivarsonion in terms of plant height and number of leaves,the treatment of plastic containtment just hasreal effect only on the number of leaves at 40 DAP. However, it has not real effect on height of the plants, and the treatmentshas real effect on theyields increasing of onion including the numbers of leaves at 40 HST and had no real effect on the numbers of fresh tuber clump, fresh tuber per 5 clumps.The aims of the research was to learn and know the effect of containment and mulch on growth and yield of Napu red onion cultivar.Â Keywords : Cultivar Napu, Mulch, Onions,Â and Plastic Sheiter.